CBSBS: A classification-based size-based scheduling and its application in industrial network - Zhiqiang He; Yongjun Lin (International Journal of Distributed Sensor Networks)
Integration of industrial control network and normal office network makes Ethernet to be widely used in industrial control. The improvement of industrial Ethernet service quality has become a hot research topic because the traditional Ethernet does not optimize the performance for industrial use. The main ideas related to research results are improving the link layer protocols or the scheduling algorithms. The method of improving scheduling algorithm is more suitable for integration of industrial and office network because it does not need to modify the link layer protocol, and it can easily realize the compatibility between office network and industrial network. The size-based scheduling proves to be effective for improving the forwarding performance of small packets (such as industrial packets). One of the newest research results of size-based scheduling is least attained recent service. Least attained recent service optimizes the queuing algorithm by applying historical accumulation factor and decay cycle factor. Least attained recent service improves the forwarding performance of small data flows significantly in data link access. But the application of the two factors in least attained recent service also results in the problem of high memory occupancy rate and unstable performance. We analyzed the cause of least attained recent service problems and designed a classification-based size-based scheduling algorithm according to the quality-of-service requirements of office and industrial networks integration. The tests prove that classification-based size-based scheduling algorithm, which can keep basic characteristics of size-based scheduling algorithm, reduce the memory consumption, and provide more stable forwarding performance than traditional least attained recent service, is an effective algorithm that can provide quality of service in the industrial network and office network integration applications.